If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6f + -9f = 15 Combine like terms: -6f + -9f = -15f -15f = 15 Solving -15f = 15 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '-15'. f = -1 Simplifying f = -1
| 15c+1c+21c= | | 61h=9.3-3.2h | | 7y-10y+6=9 | | x^3-4x+x+6=0 | | 7k-5=19 | | cot^2x=-2 | | 2(4x-3)+10=-6(-x+1)-12 | | 1600-320x+12x^2=0 | | 0.7x-0.6x-9=6 | | 32=1.60x | | K-16=2 | | 2(x+3)+7=9 | | R+R^2=24 | | (3m+8)3+m= | | X^2-31x-30=0 | | 2(9x-1)=-3(5-9x)+2 | | 3n-5=7n+12 | | 2x^2*3y= | | e/0.6-9=16 | | (0)=-14x+7 | | 6(7x+2)=42x+12 | | 6x+8x-57=95-5x | | 5=bx+c | | -14x^0+46x-12=0 | | 10-2u=4 | | 4c-5=3c | | (9+m)2m= | | 0.07(6t-5)=0.42(t-3)+0.91 | | 8a^2+32a=40 | | 2cot^4x-6cot^2x+4=0 | | v-(-7)=-10 | | 6x^2+31x+5=(6x-1) |